Exploring AEC education through collaborative learning. Issue 5 (9th September 2014) - T.W. Chan, Caroline; Sher, William
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – There is concern that traditional teaching methods (including lectures and tutorials) do not prepare graduates with the generic employability skills required by the construction industry. This has motivated architecture, engineering and construction (AEC) academics to consider the use of student-centred approaches like collaborative learning. However, the effectiveness of collaborative learning approaches has not been widely examined in AEC education. The purpose of this paper is to provide empirical results on the benefits and barriers of collaborative learning from AEC students' perspective. Design/methodology/approach – From a questionnaire survey conducted with Associate Degree students who studied in four AEC programmes at a university in Hong Kong, 621 valid responses were received. Descriptive statistics were used to test these data for any significant agreement or disagreement between respondents. Findings – All AEC students agreed that collaborative learning benefited them in building their academic knowledge and generic skills. However, the degree of agreement about their generic skills development differed between programmes. The findings of this study highlight the effectiveness of collaborative learning as a means of developing students' employability skills. Research limitations/implications – First, the analysis of the benefits of collaborative learning is based on students' perceptions rather than objective measures of learning gains. Although research suggests that self-reported measures of learning are valid indicators of educational and skill gains, the possibility of individual's bias or peer influence in the responses cannot be discounted. Second, the study does not take into account the teachers' instructional skills that may affect the effectiveness of collaborative learning. To minimize the impact of different tutors on students' learning experiences, standardized delivery mode and course materials were adopted in the surveyed courses. Practical implications – From the findings presented, collaborative learning is a viable tool which assists in improving both the technical and generic employability skills of students. To allow students to appreciate collaboration in a practical context, multi-disciplinary collaborative assignments can be integrated in AEC curricula. Through collaboration with other disciplines, students can understand the ways of working with other professionals. At the same time, AEC educators can apply collaborative learning to strengthen specific collaborative skills. To maximize the benefits of collaborative learning, teachers should arrange regular meetings and counseling sessions with students to ensure participation from each individual. Social implications – The findings contribute practical insights about collaborative learning and, in particular, the learning attitudes and perceptions of Chinese students and engineering students. Whilst the findings are different to some studies which describe Chinese students as being influenced by the Confucian Heritage culture, and preferring competitive rather than collaborative learning, more detailed studies about collaborative learning dynamics among students from different ethnic backgrounds should improve the design of collaborative learning environments for the students. Originality/value – The findings provide confidence to AEC academics to incorporate collaborative learning activities in their courses. Mapping students' generic skills development between programme of study provides indicators that highlight the use of collaborative learning for different generic skills development in different AEC programmes. The results of this study provide useful information for AEC teachers, assisting them to design multi-disciplinary collaborative learning curricula.